Development of Islamic Cultural History Teaching Materials for Grade 2 Students at SDN Mayangan 2, Probolinggo City - Moch. Salman Alfarizi; Saiful Amien (Al-Fadlan: Journal of Islamic Education and Teaching, 2024)
Teaching materials are one of the important components that can affect the quality of learning. This study aims to develop innovative, relevant, and appropriate SKI teaching materials for students. This study uses a library research method, by conducting a descriptive-analytical approach with a literature review type. The teaching materials of Islamic Cultural History for grade 2 students at SDN Mayangan 2, Probolinggo City, can be concluded that the material covers various important aspects, such as belief in the truth of the story of Prophet Ibrahim and his biography, his preaching, and values ​​such as the attitude of being willing to sacrifice, obeying, and being obedient to Allah SWT.